The juvenile justice system in Ukraine: searching for а consensus paradigm. - Плахова, О. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2015)
The article deals with a wide and a narrow approach to juvenile justice system. The author focuses on the narrow sense of the juvenile justice system as a social technology which aimed at rehabilitation, rather than retributive justice in relation to juvenile offenders. This approach eliminates the possibility of interference in family relations and it is a consensus in a confrontation between supporters and opponents of the juvenile justice system. It’s emphasizes the need for a clearer definition of the goals and objectives of the juvenile justice system, taking into account the practice of foreign countries, as well as the specifics of socio-cultural features of Ukrainian families.